2019
DOI: 10.3390/ijms20020258
|View full text |Cite
|
Sign up to set email alerts
|

Human Germ Cell Tumors are Developmental Cancers: Impact of Epigenetics on Pathobiology and Clinic

Abstract: Current (high throughput omics-based) data support the model that human (malignant) germ cell tumors are not initiated by somatic mutations, but, instead through a defined locked epigenetic status, representative of their cell of origin. This elegantly explains the role of both genetic susceptibility as well as environmental factors in the pathogenesis, referred to as ‘genvironment’. Moreover, it could also explain various epidemiological findings, including the rising incidence of this type of cancer in Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 162 publications
4
101
0
2
Order By: Relevance
“…When refering to testicular cancer one is often referring, in fact, to testicular germ cell tumors (TGCTs), since they represent more than 95% of all testicular neoplasms. Despite not being a common malignancy, they are the most frequent solid cancers among young adult Caucasian men and incidence is increasing worldwide due to changes in lifestyle, which is in line with the proposed genetic and environmental model ("genvironment") of the disease [160][161][162].…”
Section: Major Clinical Challengessupporting
confidence: 63%
See 1 more Smart Citation
“…When refering to testicular cancer one is often referring, in fact, to testicular germ cell tumors (TGCTs), since they represent more than 95% of all testicular neoplasms. Despite not being a common malignancy, they are the most frequent solid cancers among young adult Caucasian men and incidence is increasing worldwide due to changes in lifestyle, which is in line with the proposed genetic and environmental model ("genvironment") of the disease [160][161][162].…”
Section: Major Clinical Challengessupporting
confidence: 63%
“…TGCTs are very heterogeneous [163], reflecting a complex tumor model that closely resembles developmental biology phenomena. Type II TGCTs (the most common) derive from a precursor lesion named germ cell neoplasia in situ (GCNIS), which then evolves into two big categories, seminomas (SEs) and non-seminomas (NSs), the latter being further divided into embryonal carcinoma (EC), postpubertal-type yolk sac tumor (YST), choriocarcinoma (CH) and postpubertal-type teratoma (TE) [162,164]. An integrated approach to TGCTs [165] has evidenced remarkable differences in methylation profiles between SE and NS, and also confirmed the value of the miR371-373 cluster in these tumors.…”
Section: Major Clinical Challengesmentioning
confidence: 99%
“…Likewise, in an evaluation of miR-371a-3p expression levels in GCT subtypes by RNA extraction from formalin fixed paraffin embedded orchiectomy specimens, Vilela-Salgueiro et al revealed a strong expression in all GCT subtypes except teratoma [25]. The reason for the non-expression of the miR by teratoma is probably related to the analogies of GCT biology and the human embryonal development [34,35]. While most of the GCT subtypes mimic early developmental stages of embryonal development and accordingly retain their biochemical characteristics including the microRNA profile of stem cells, the teratoma subtype represents a more advanced and more mature histological subtype that has lost all of the biochemical characteristics of stem cells particularly the typical expression of miR-371a-3p [36].…”
Section: Intracellular Localization Of Mir-371a-3p By Ishmentioning
confidence: 99%
“…2 TGCTs are broadly divided into two main groups: those derived from the precursor lesion germ cell neoplasia in situ (GCNIS), generally called postpubertal-type tumors; and those unrelated to GCNIS. 3 The first group, on which we will be focusing, corresponds to type II TGCTs (within the developmental-based classification of these neoplasms 4,5 ), and include seminomas (SE) and non-seminomas (NS). NS can be further subdivided into embryonal carcinoma (EC), teratoma (TE), yolk-sac tumor (YST), and choriocarcinoma (CH), which are frequently admixed in the so-called mixed tumors.…”
Section: Introductionmentioning
confidence: 99%